Antifungal Effects of Water, Alcoholic and Phenolic Extracts of Seeds and Leaves of Sorghum bicolor (L.) Moench on Fusarium solani and F. poae - A Ataei Azimi; B Delnavaz Hashemloian; A Mansoorghanaei (Institue of Medicinal Plants, ACECR, 2007)
Background: Fusarium from Tuberculariacea family is listed as one capable of causing mycetomas in human, animals and plants.   Objective: In this investigation, antifungal activity of water, metanolic and phenolic extracta of seeds and leaves of sorghum bicolor were studied on Fusarium poae and F. solani.   Methods: Primarily, the crude water extracts at 7 concentrations of 0-50mg/l were tested. Results: The concentrations of 10 and 40 mg/l, showed inhibitor effects on F. poae. The methanol extracts at different concentrations were tested. 20, 30and 40 mg/l (Specially 30 mg/l) of metanolic extract showed antifungal activity agianst F. poae. The phenolic compouns (0 - 25mg/l) showed high antifungal activity on F. solani and F. poae.